Nanoindentation system for material properties identification / Teo Adrian Wei Hong, Yeap Gik Hong and Loo Wei Jie - Teo, Adrian Wei Hong; Yeap, Gik Hong; Loo, Wei Jie (UiTM Press, 2015)
This paper proposed to design a nanoindentation system with the intention to identify material properties without spalling. The system is designed to perform simulation based on the load-depth curve data collected from NanoTestTM. The hardness results are compared with Brinell hardness test and NanoTestTM for the same materials; i.e. brass, mild steel, aluminium and copper. Oliver-Pharr and Joslin-Oliver methods are selected to measure the material properties. Both selected methods require indentation load, impression area and depth to fulfil the material properties calculation while these signals are collected through a displacement sensor and an actuator. The results collected indicate that the spall of material rate, which can be reduced by decreasing the indentation load while maintaining the indentation depth at a longer dwell time. The theoretical simulation result of Joslin-Oliver method which neglects substrate effect acquired an average error rate of 7.823% whereas Oliver-Pharr method acquired an average error rate of 6.355%, both with comparison against NanoTestTM machine. The experiments have been performed using same materials; i.e. brass, aluminium, copper and mild steel.